THE COSSACKS’ BORDERING PROCESS IN THE CIVIL WAR. FILMIC REPRESENTATIONS - Olga GRĂDINARU (Territorial Identity and Development, 2020)
The Russian Revolution(s) and the Russian Civil War represent topics revisited by the recent Russian media and film-making. Mikhail Sholokhov’s novel And Quiet Flows the Don as a masterful case of fictionalisation of historical events is the basis for four subsequent film adaptations. Whereas the destiny of the Russian Cossacks is a generous theme, we would like to focus on the filmic representation of Cossacks’ bordering process in the Civil War. Two Soviet film adaptations and two post-Soviet ones present in different manners the impact of the shifting borders on people’s lives during the Russian fratricide war. Tzar’s abdication had caused confusion in the midst of the Cossack population loyal to the state father figure, while contributing afterwards to a territorial identity construction and a fight to obtain and maintain the autonomy of the Cossack region. Soviet and post-Soviet directors’ approaches of the geographical, mental and cultural borders during the Civil War in the Cossack region offer insights into the debatable loyalties and multiple sides shifting. The analysis of the four film adaptations is focused on concepts such as questioned loyalty, divisive Cossack territorial identity, nuanced and shifting identity and active/ passive territoriality. We argue that the Cossacks’ territorial identity and their bordering process is differently reflected in subsequent film adaptations of the novel.